Bortezomib‐based therapy is effective and well tolerated in frontline and multiply pre‐treated Waldenström macroglobulinaemia including BTKi failures: A real‐world analysis. Issue 4 (20th October 2022) - Khwaja, Jahanzaib; Uppal, Encarl; Baker, Robert; Trivedi, Kajal; Rismani, Ali; Gupta, Rajeev; Proctor, Ian; Kyriakou, Charalampia; D'Sa, Shirley
Abstract: Waldenström macroglobulinemia (WM) is a rare, incurable low grade lymphoma following a relapsing trajectory. Management strategies have evolved with the introduction of targeted therapy including new classes of Bruton tyrosine kinase inhibitor (BTKi). Treatment may however be limited particularly at relapse by a lack of drug availability and tolerability. We assessed the real‐world efficacy and tolerability of bortezomib‐containing regimens in patients with WM at frontline and relapse including those with prior BTKi resistance. Forty‐one patients were identified with 44 bortezomib‐containing regimens administered ( n = 12 frontline, n = 32 relapse). Of patients treated at relapse, the median prior lines of therapy was 3 (range 1–7). 24% (10/41) of the cohort were refractory or intolerant to BTKi prior to bortezomib delivery. The median follow‐up after bortezomib administration was 34 months (range 0‐131). Overall response rate was 88%; 2‐year overall survival and progression‐free survival were 90% (95% confidence interval [CI] 73–96) and 76% (95% CI 55–87), respectively. Median time‐to‐next‐treatment was 66 months. Neuropathy (grade 1–2) occurred in 24% (8/34) and did not result in treatment cessation in any case. Gastrointestinal disturbance occurred in 7% (3/41). Treatment discontinuations were rare (1/44; 2%), suggesting a manageable safety profile. Major response rate was comparable in those with prior BTKi compared with those without (75% [6/8] vs 84% [27/32], p = 0.61). Bortezomib should be considered as a treatment modality particularly in those who are refractory to BTKi.